Effect of family presence during teaching rounds on patient's anxiety and satisfaction in cardiac intensive care unit: A double-blind randomized controlled trial - Ali Ansari Jaberi; Fahimeh Zamani; Ali Esmaeili Nadimi; Tayebeh Negahban Bonabi (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: The family members' presence during teaching rounds is introduced as a challenging issue. The outcomes of family presence during teaching rounds in adult care settings is an under investigate issue. The propose of this study was to determining the effect of family presence at teaching rounds on patient's anxiety and satisfaction in cardiac intensive care unit (CICU). MATERIALS AND METHODS: In this double-blind randomized controlled trial, 60 patients who were hospitalized in CICU were selected based on inclusion criteria and then assigned into 2 groups (with and without family members presence during teaching round), equally by the random minimization method. The patient's anxiety score was measured before and after rounds on the Spielberger State-Trait Anxiety Inventory (STAI). Furthermore, the patient's satisfaction about various clinical aspects of round was measured by a self-reported questionnaire. The data were analyzed by SPSS software using Kolmogorov-Smirnov test, Chi-square test, independent sample and paired sample t-test, at the significance level of 0.05. RESULTS: The study groups were similar in terms of demographic variables. In the family members presence group, the STAI score significantly decreased after intervention (P = 0.001). Furthermore, in this group, the after-intervention STAI score was significantly lower than family absence group (P = 0.011). The mean changes of patient's satisfaction about quality of round score in family member presence group were significantly higher than family absence group (P = 0.001). CONCLUSIONS: Family presence during teaching rounds led to patient's lower anxiety and higher satisfaction score.